Comparison of scaffolds fabricated via 3d printing and salt leaching: In vivo imaging, biodegradation, and inflammation - Kwon, Doo Yeon; Park, Joon Yeong; Lee, Bun Yeoul; Kim, Moon Suk (Polymers, 2020)
In this work, we prepared fluorescently labeled poly(ε-caprolactone-ran-lactic acid) (PCLA-F) as a biomaterial to fabricate three-dimensional (3D) scaffolds via salt leaching and 3D printing. The salt-leached PCLA-F scaffold was fabricated using NaCl and methylene chloride, and it had an irregular, interconnected 3D structure. The printed PCLA-F scaffold was fabricated using a fused deposition modeling printer, and it had a layered, orthogonally oriented 3D structure. The printed scaffold fabrication method was clearly more efficient than the salt leaching method in terms of productivity and repeatability. In the in vivo fluorescence imaging of mice and gel permeation chromatography of scaffolds removed from rats, the salt-leached PCLA scaffolds showed slightly faster degradation than the printed PCLA scaffolds. In the inflammation reaction, the printed PCLA scaffolds induced a slightly stronger inflammation reaction due to the slower biodegradation. Collectively, we can conclude that in vivo biodegradability and inflammation of scaffolds were affected by the scaffold fabrication method.
Keywords: 3-D printing; 3D Structure; Caprolactone; In-Vivo imaging; Salt leaching; Salt-leaching method; Scaffold fabrication methods; Three-dimensional (3D) scaffolds; Biodegradation; In vivo imaging; Printing; Salt-leaching; Scaffold